Advanced techniques in soil microbiology (Springer, 2007)
The techniques and procedures have been selected with the aim of offering practical guides for immediate use in the laboratory. The systems investigated range from individual molecules and cells to entire eukaryotic organisms, with a focus on bacteria, fungi, mycorrhiza, and higher plants. This volume of state-of-the-art, practice oriented methods will be of great use both to the first-timer and to the experienced scientist.